PENGEMBANGAN MODUL ELEKTRONIK (E MODUL) KETERAMPILAN BERBAHASA DAN SASTRA INDONESIA SD UNTUK MENINGKATKAN KETERAMPILAN MENYIMAK MAHASISWA PGSD - Wahyu Nuning Budiarti; Mawan Akhir Riwanto (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2021)
This development research developed one of the learning media needed during the Covid 19 pandemic, namely an electronic module which is the development of a module that is easier to use, easy to carry, concise and practical by lecturers and students. The module for Elementary School Indonesian Language and Literature Skills for PGSD students was developed so that students can better apply the language skills learning aspects of listening in their ability to synthesize. The research method used 10 steps of Borg and Gall's development research grouped into 4 procedures. The four procedures are. (1) Initial research (2) Product Development, (3) Product testing and revision, and (4) final stage. The data is obtained by analyzing the ratings by users, material experts, and media experts. The result obtained is that the feasibility value by the experts reaches a value of 90% from material experts and 89% from media experts with very valid criteria and is achieved in the second stage. Student response is very good with a score of 74.14%. Pre test results are? and the post test results after using the product being developed are 22,5%. The use of e-modules for learning is proven to improve students' listening skills and shows that this language skills learning module is feasible to use.